EWALUACJA NARZĘDZI BADANIA NUDY NA ZAJĘCIACH PRAKTYCZNEJ NAUKI JĘZYKA ANGIELSKIEGO Z PERSPEKTYWY MAKRO I MIKRO - Joanna Zawodniak; Mirosław Pawlak; Mariusz Kruk (Neofilolog, 2019)
Although boredom is among the most frequently experienced academic emotions, it has received surprisingly little attention from L2 researchers and teachers. This paper aims to discuss and evaluate the existing quantitative and qualitative instruments that can be used for examining boredom in practical English classes. It will start with a brief overview of the causes and manifestations of boredom in the language classroom. This will be followed by the presentation of the methodology of three empirical studies which will serve as a basis for highlighting the strengths and weaknesses of the data collection tools employed. Finally, an attempt will be made to delineate future research directions in the study of boredom in the L2 classroom and to illuminate the methodological choices available to researchers in this respect.